Circuit design of buck-voltage converter with digital control system - Zheliazkov, Yehor (Technology audit and production reserves, 2020)
The objects of research are processes in electrical scheme and enormous digital control systems in converter. One of the most problematic things is transfer and energy change in converter for current and voltage in order to reach certain value of digital range with a minimal percentage of error. This work explores buck-voltage converter with digital control system. An enormous considered procedure of projecting electrical scheme. There was described electrical scheme with a control system, which, thanks to the digital system, provides dates with more accuracy in the output of converter, among them: assignment of certain digital range of output voltage and system’s impact on working scheme. During the research there was used selection of hardware features and software tools, accepting peripheral devices, which let quickly and simply set up microcontroller for certain operating mode and to realize controlling system for buck converter in a programmatic manner. There was analyzed procedure of solving and choosing of the certain parts of electrical scheme, where was used to construct: – microcontroller for receiving, processing and issuance of information in electrical scheme; – driver operating and analog-to-digital conversion; – driver for control of the switches – basically transistors; – components of the buck-converter circuit. There is description and schematic choice of the certain parts of the scheme. There was included switch, capacitor and diode for buck converter; certain range of the frequency and voltage for microcontroller; control of the power keys of the circuit with the corresponding operating parameters for driver. There was received a system, which in prospect will become a basis to step down voltage value to the certain level. This is because defined method has a set of features, particularly digital regulation system with a discrete step and analog-to-digital converter in the capacity of feedback. Therewith provides possibility for receiving more accuracy value. In comparison with analogic buck converters, this converter has voltage parameter with fractional error.